Living in Ethnic Areas or Not? Residential Preference of Decimal Generation Immigrants among Asian Indians, Japanese, Chinese, Koreans, Filipinos, and Vietnamese - Shuang Li; Weiwei Zhang (Social Sciences, 2021)
The present study examines the spatial assimilation patterns of immigrants who arrived as children. The main objective is to predict the likelihood of living in ethnic areas for decimal generation immigrants (1.25, 1.5, and 1.75) among Asian Indians, Japanese, Chinese, Koreans, Filipinos, and Vietnamese. Using 2013–2017 5-Year ACS Estimates and IPUMS, it applies the measure of local spatial clustering (the Local Moran’s I statistic) to identify ethnic areas and the logistic regression model to assess the effects of immigrant generational status, cultural, and socioeconomic assimilation on the probability of living in ethnic areas. The findings show that the 1.25 and 1.5 decimal generation immigrants of Chinese, Filipinos, Japanese, and Koreans demonstrate higher propensities of living in ethnic areas compared to the first generation of each ethnic group, respectively. Meanwhile, their Asian Indians and Vietnamese counterparts show spatial assimilation. Regardless of generational effects, English language ability positively relates to the probability of living in nonethnic areas, whereas economic assimilation indicators reveal mixed results. We found substantial evidence for resurgent ethnicity theory and some support of spatial assimilation model, indicating the ethnic disparity in spatial assimilation patterns among Asian immigrants. Our paper highlights the nonlinear assimilation patterns among Asian decimal generations. Results suggest that, for Asian immigrants in the U.S., age-at-arrival and ethnicity are both significant predictors of residential preference.